Kepuasaan Masyarakat Terhadap Penyelenggaraan Urusan Pemerintahan Absolut Di Daerah - Nazaki, Nazaki (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2016)
Governance in principle is in order to serve the public good in the form of service of goods, services, or administrative. Their various weaknesses in service delivery adversely affects the quality of care received by the public. As a recipient of the service, the community has an important role in assessing whether or not a quality service through the level of satisfaction felt. This study discusses the level of community satisfaction in the conduct of government affairs asbsolut religious sector, in particular the provision of services KUA in Tanjungpinang. Through survey research methods, known level of public satisfaction towards the provision of services KUA in Tanjungpinang obtain the value of good quality, with an index value of 76.75. The element certainty the cost of services should be prioritized in improvement service quality.